THE RELATIONSHIP OF NITRATE AND PHOSPHATE CONTENT WITH ABUNDANCE OF EPIPHYTE DINOFLAGELLATE ON SEAGRASS Enhalus acoroides IN THE WATERS OF PONCAN GADANG ISLAND WATERS - Erfana Romauli Lumbantoruan; Zulkifli Zulkifli; Yusni Ikhwan Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTDinoflagellate isa large of microalgae groups. Its abundance was dependent on nitrate and phosphate content. The research was conducted in September 2018 that located at waters of Poncan Gadang Island, Central Tapanuli Regency. The aims of this research was to analyze nitrate and phosphate content, identification of species of epiphyte dinoflagellates, and the relationship between nitrate and phosphate content with abundance of epiphyte dinoflagellate on seagrass Enhalus acoroides were analyzed. Apparently the highest of nitrate content found at station I and II on 0.0402 mg/l, the lowest found at station III on 0,0367 mg/l. the highest of phosphate content found at station III on 0,0995 mg/l, the lowest found at station I on 00678 mg/l. It revealed that 3 species of epiphyte dinoflagellate foundwhich are Amphidinium sp., Gambierdiscus sp. and Prorocentrum sp. The highest of abundance epiphyte dinoflagellate found at station II on 1245,90 sel/g and the lowest found at station III on 767,13 sel/g. The relationship between the nitrate content with abundance of epiphyte dinoflagellate has a positive relationship with the regression equation y = 294.55 + 1121.5x, while the relationship between the phosphate content with abundance of epiphyte dinoflagellate has a negative relationship with the regression equation y = 488.54 + (-1801.7x).Keywords : Epiphyte Dinoflagelates, Nitrate , Phosphate, Poncan Gadang Island.